Letter to the editor: radiomics signature for dynamic monitoring of tumor-inflamed microenvironment and immunotherapy response prediction - Shuixing Zhang; Yuhao Dong (Journal for ImmunoTherapy of Cancer)
We read with great interest the article by Bernatowicz et al. Despite the promising findings, we would like to highlight several concerns regarding the methodology and interpretation of the results that warrant further discussion, including the stability of radiomic features across pan-cancer types, the optimal threshold for CT-TIME (tumor immune microenvironment) scores, the biological interpretability of radiomic models, and the survival tail effect of immunotherapy responses.